2016
DOI: 10.4103/0019-509x.197743
|View full text |Cite
|
Sign up to set email alerts
|

An audit of cytoreductive surgeries in ovarian cancer from a rural based cancer center

Abstract: Optimal cytoreduction may improve PFS in advanced ovarian cancer patients and needs to be done even if it mandates an ultra-radical surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Complete resection of tumour was achieved in 61.5% which is higher compared to the 54.1% of the Norfolk and Norwich Hospital study (12). Similar studies have found that complete resection is signi cantly associated with increased survival and it is one of the main reasons why the ultra-radical approach has been utilized more and more in recent years (13)(14)(15)(16)(17). Incorporating surgery, even for those patients with a greater tumour burden and more disseminated disease who may require more complex procedures and more resources in terms of theater time and hospital stay, seems to be associated with a signi cant prolongation of the patients' overall survival compared with chemotherapy alone (18).…”
Section: Discussionmentioning
confidence: 81%
“…Complete resection of tumour was achieved in 61.5% which is higher compared to the 54.1% of the Norfolk and Norwich Hospital study (12). Similar studies have found that complete resection is signi cantly associated with increased survival and it is one of the main reasons why the ultra-radical approach has been utilized more and more in recent years (13)(14)(15)(16)(17). Incorporating surgery, even for those patients with a greater tumour burden and more disseminated disease who may require more complex procedures and more resources in terms of theater time and hospital stay, seems to be associated with a signi cant prolongation of the patients' overall survival compared with chemotherapy alone (18).…”
Section: Discussionmentioning
confidence: 81%
“…The Endometrial cancer is one of the most common cancers in women worldwide and the death rate for this cancer has been increasing with an average increase of 1.4% per year between the years 2005 and 2014 (Miller et al, 2016). Older age, higher stage, grade, tumor size, lymph node status, race, comorbidities, obesity and treatment methods are associated with lower endometrial cancer survival (Dessai et al, 2016;Bregar et al, 2017;Nicholas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%